PENDEKATAN IN VITRO DALAM PENILAIAN BIOAVAILABILITAS ZAT BESI PANGAN: In vitro Approaches in Assessing Dietary Iron Bioavailability - Yunna Teodor; I Kadek Adi Indrawan; Kelvin Then; Kent Pranata Tjandra; Rike Tri Kumala Dewi; Dwining Putri Elfriede (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2026)
Iron availability in foods was determined not only by total iron content but also by its bioaccessibility and bioavailability. This review aimed to evaluate the role of in vitro testing methods in assessing iron availability from various food products and to identify food matrix factors influencing its absorption. The methods discussed included static gastrointestinal digestion simulation, total iron analysis using Atomic Absorption Spectroscopy (AAS) or Inductively Coupled Plasma (ICP), and the Caco-2 cell model measuring ferritin formation as an indicator of bioavailability. The findings indicated that total iron content did not necessarily correlate with biological absorption. Several factors, such as fermentation, fortification, phytate degradation, and the addition of ascorbic acid, were found to significantly enhance iron availability, particularly in plant-based food matrices. These results suggested that food processing and formulation strategies played a critical role in improving iron uptake. Among the reviewed approaches, the combination of in vitro gastrointestinal digestion and Caco-2 cell models was identified as the most comprehensive method for future product development, as it allows simultaneous evaluation of bioaccessibility and cellular uptake. In conclusion, in vitro approaches were considered practical and efficient preliminary tools in the development and evaluation of iron-rich food products before proceeding to in vivo studies.